Identification and Expression of Two Novel Cytochrome P450 Genes, CYP6CV1 and CYP9A38, in Cnaphalocrocis medinalis (Lepidoptera: Pyralidae). Issue 1 (20th April 2015) - Chen, Jun; Li, Chuan; Yang, Zhifan
Abstract : Cnaphalocrocis medinalis Güenée can cause severe losses in rice. Cytochrome P450s play crucial roles in the metabolism of allelochemicals in herbivorous insects. Two novel P450 cDNAs, CYP6CV1 and CYP9A38, were cloned from the midgut of C . medinalis . CYP6CV1 encodes a protein of 500 amino acid residues, while CYP9A38 -predicted protein has 531 amino acid residues. Both cDNA-predicted proteins contain the conserved functional domains for all P450s. Phylogenetic analyses showed that CYP6CV1 is grouped in the cluster containing CYP6B members, while CYP9A38 is in the cluster including CYP9 members. However, both clusters are contained in the same higher lineage. Homologous analysis revealed that CYP6CV1 is most similar to CYP6B8, CYP6B7, CYP6B6, CYP6B2, and CYP6B4 with the highest amino acid identity of 41%. CYP9A38 is closest to CYP9A17, CYP9A21, CYP9A20, and CYP9A19 with the highest amino acid identity of 66%. Studies of temporal expression profiles revealed that CYP9A38 showed a steady increase in mRNA level during the five instar stages, but a low-expression level in pupae, and then presented at a high-expression level again in adults. Similar expression patterns were obtained with CYP6CV1 . In the fifth instar larvae, CYP6CV1 was mainly expressed in midgut and fat bodies, whereas CYP9A38 was mainly expressed in midgut. Expression studies also revealed a 3.20-fold over-expression of CYP6CV1 and 3.54-fold over-expression of CYP9A38 after larval exposure to host rice resistance. Our results suggest that both CYP6CV1 and CYP9A38 may be involved in detoxification of rice phytochemicals.